Validity and reliability study of charity hazard scale - ÇİFTÇİOĞLU, GÖKÇEN ALEV (My University, 2023)
Safety culture, which enables people to think proactively, is a concept that is still developing in Turkey. From a disaster management point of view, the concept of safety culture provides the formation of a culture covering the implementation of the risk management phase. Therefore, it is possible to state that the concept of charity hazard poses a serious threat to the safety culture. Thus, the concept of charity hazard is of great importance in the formation of safety culture in the fields of occupational health and safety, emergency aid and disaster management. In this context, the present study aims to develop a valid and reliable scale for the concept of charity hazard. As a result of the analyses conducted with 532 participants residing in different cities across Turkey and working in different fields; the factor loadings of the items in the scale ranged between 0.51 and 0.95 and the total variance explained was calculated as 63.244 %. According to the results of the confirmatory factor analysis, the charity hazard scale consists of 3 factors and 10 items (X2/df = 2.346, RMSEA: 0.050, SRMR: 0.048, NFI: 0.97, NNFI: 0.97, CFI: 0.98, GFI: 0.97, AGFI: 0.95). The internal consistency of the scale was calculated as 0.758 and item-total correlations ranged between 0.318 and 0.554. In conclusion, the analyses show that the charity hazard scale developed is a valid and reliable measurement tool.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Charity hazard; Safety culture; Occupational safety; Disaster management; Validity; Reliability